2022-VA-628-ESGO Inferior Vena Cava injury during laparoscopic para-aortic lymphadenectomy. (20th October 2022) - Pandraklakis, Anastasios; Giovannopoulou, Eirini; Oikonomou, Maria D; Saliaris, Konstantinos; Saso, Srdjan; Lathouras, Konstantinos
Abstract : Introduction/Background: Laparoscopic para-aortic lymphadenectomy is a challenging surgical procedure for Gynaecological Oncologists and require advanced laparoscopic skills and good knowledge of the retroperitoneal anatomy and landmarks. Our aim is to present our experience in managing a major vascular injury complication during advanced laparoscopic surgery. Methodology: The indication for the laparoscopic para-aortic lymphadenectomy was endometrioid endometrial cancer grade 3 stage 1B (FIGO) in a 65-year-old patient with BMI of 36. Not proper identification of a perforating vein between during dissection of precaval nodes at the level above the bifurcation of the inferior vena cava (IVC) resulted in tearing the IVC and ongoing significant hemorrhage. Results: Amongst different available surgical or more conservative techniques on the management of a laparoscopic hemorrhagic complication we decided to use a hemostatic agent called Floseal, which is a mixture of flowable gelatin matrix and human-derived thrombin component. Hemostasis achieved efficiently after the application of the hemostatic agent avoiding the use of surgical techniques which are more risky for further extension of the IVC tearing. Conclusion: Prevention of complications during a complex surgical complication is only the one 'side of the coin'. Surgeons should be well experienced and ready not only to avoid but also to deal with severe perioperative complications in order to offer high level quality of care on their patients. In order to manage these stressful events requirements such as teamwork, experience, training and well organized resourced should be fulfilled.